Less is more - Cyclists-Triathlete's 30min cycling time-trial performance is impaired with multiple feedback compared to a single feedback - Bayne, F.; Gaoua, N.; Mileva, K.; Hunter, S.; Racinais, S. (Frontiers in Psychology, 2020)
Purpose: The purpose of this article was to (i) compare different modes of feedback (multiple vs. single) on 30 min cycling time-trial performance in non-cyclist`s and cyclists-triathletes, and (ii) investigate cyclists-triathlete`s information acquisition.